Non-critical uranium accumulation in soils of German and Danish long-term fertilizer experiments - Sun, Y.; Wu, B.; Amelung, W.; Christensen, B. T.; Pätzold, S.; Bauke, S. L.; Schweitzer, K.; Baumecker, M.; Bol, R. (Geoderma, 2020)
Phosphorus (P) fertilizers vary considerably in contents of uranium (U), thus raising concerns regarding U accumulation in agricultural soils. We examined U concentrations in soil from three long-term field experiments with different P fertilizer applications: Rengen (P fertilizer from basic slag, grassland, Germany), Thyrow (P fertilizer from igneous phosphate rocks, arable land, Germany) and Askov (P fertilizer from igneous phosphate rocks, arable land, Denmark). Accumulation rates were low for Rengen (1.3 µg U kg −1 yr −1 ) and Thyrow (0.6 µg U kg −1 yr −1 ) in P-treated plots compared with plots without P fertilization. These accumulation rates were ten times lower than those previously reported (mean 17 µg U kg −1 yr −1 ). Intriguingly, concentrations of acid-extractable U in the Askov topsoil increased from 1923 to 2016, regardless of whether P was added (5.1 µg kg −1 yr −1 ) or not (4.7 µg kg −1 yr −1 ). This suggests that at least part of the accumulated U originated from other sources than P fertilizers. Total U concentrations were significantly larger in the period 1985–2016 than in the period 1938–1976 in Askov soil treated with NPK but not in soils without P fertilization. Hence, long-term P fertilizer application did increase the soil U concentrations at Askov, although at a low level. The low U accumulation rates in soils from these German and Danish long-term P fertilization experiments indicate that with current management, the soil U concentration could remain at non-critical levels even on a centennial scale. This is attributed to the historic use of P fertilizers derived from sources with low U content (igneous phosphate rocks from Finland and Kola Peninsula for Askov and Thyrow, respectively, and basic slag for Rengen). Hence, U accumulation due to long-term P fertilization in agricultural soils may be alleviated by using phosphate rocks from low U sources in P fertilizer production.